Bokashi Application for Organic Farming in Manuk Mulia Village, Karo District - patriani, peni patriani (Journal of Saintech Transfer, 2022)
Berkah Mulia is a farmer group in Manuk Mulia Village, Karo Regency with 19 members. Livestock developments may cause several problems such as environmental pollution in the form of livestock manure which causes unhealthy environmental conditions. In addition, the unstable supply of chemical fertilizers and high prices are problems that are quite difficult to solve. The solution to this problem is the utilization of cattle feces in Bokashi which can improve the physical, chemical, and biological properties of the soil due to the use of excessive chemical fertilizers to improve soil quality. Bokashi is compost produced from the fermentation process or organic matter fermentation with EM4 technology. The method implemented in the community service is having interviews and discussions to find the solution for all problems. Then use teaching media in the form of banners and brochures about the method of making bokashi. Training, counseling, and mentoring are carried out by providing materials and practices for making bokashi using cow feces. The results of the activity show that this community service can increase the knowledge and skills of farmers by 84% related to making bokashi. This activity can also reduce environmental pollution and reduce the cost of purchasing chemical fertilizers so that horticultural crop production increases.